2022
DOI: 10.1177/21582440221116103
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Instructional Coaches’ Practices in Professional Learning Communities

Abstract: In this study, we investigated Texas teachers’ perceptions of instructional coaches’ (ICs) practices that improve professional learning communities (PLCs) to enhance teachers’ instructional capacities. The study’s participants included 67 teachers from rural, urban, and suburban school districts across the state of Texas. They enrolled in a virtual professional development (VPD) module related to improving instruction in high needs schools. Data were collected from participants via an open-ended survey. To ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 26 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…They go on to name ways that coaches can explicitly accomplish this, particularly by sharing instructional strategies. Providing resources or strategies is not enough however, and coaches are also needed to facilitate collaboration between teachers and lead them in intentional discourse as needed (Elfarargy et al, 2022). The district involved in Voelkel et al (2023) would likely concur with the assertion and found that coaches "can be instrumental in the successful implementation" of their PLC model (p.155).…”
Section: Utilizing Instructional Coaches To Support Collaboration Dur...mentioning
confidence: 99%
See 4 more Smart Citations
“…They go on to name ways that coaches can explicitly accomplish this, particularly by sharing instructional strategies. Providing resources or strategies is not enough however, and coaches are also needed to facilitate collaboration between teachers and lead them in intentional discourse as needed (Elfarargy et al, 2022). The district involved in Voelkel et al (2023) would likely concur with the assertion and found that coaches "can be instrumental in the successful implementation" of their PLC model (p.155).…”
Section: Utilizing Instructional Coaches To Support Collaboration Dur...mentioning
confidence: 99%
“…Building on these ideas, collaboration via the professional learning community structure may a very effective form. Elfarargy et al (2022) argued that collaboration in PLCs allows for "various instructional interactions such as questioning, brainstorming, and reflecting" (p.9). Collaboration also needs to be present in the form of "active learning" (Stepp & Brown, 2021).…”
Section: Collaboration In the Form Of Professional Learning Communitiesmentioning
confidence: 99%
See 3 more Smart Citations